Predicting the CTE & hardness for directed energy deposition of functionally graded WC-SS316L Coatings - Ndinisa Sindi; Sacks Natasha (MATEC Web of Conferences, 2022)
One of the key components in the design of wear resistant coatings for directed energy deposition is the analysis of the thermo-mechanical properties within the substrate-coating interface. The coefficient of thermal expansion (CTE) and the mismatch are crucial due to their significant influence on the structural integrity and operational performance of the coating. In this study, a four-layered functionally graded tungsten carbide (WC)-316L stainless steel composite coating was designed using a rule-of-mixtures approach for manufacture by directed energy deposition. Two theoretical models were employed to predict the CTE and micro-hardness as a function of increasing volume fraction of WC particles. According to the graded concentrations predicted from the linear models, the four-layer coating exhibits a good hardness with minimal CTE mismatch.